Farmers’ Preferences and Willingness to Pay for Attributes of Integrated Pest Management Methods Against Spodoptera frugiperda (Lepidoptera: Noctuidae) in Benin - HOUNGBO, Sidol; ZANNOU, Afio; Zossou, Espérance; ZANMENOU, Calmette S. G.; AOUDJI, KOSSI NOUNAGNON AUGUSTIN; SINZOGAN, Antonio A.; SIKIROU, Rachidatou; AHANCHEDE, ADAM (My University, 2021)
In response to the invasion of Spodoptera frugiperda (J.E. Smith) in Africa, farmers rely mainly on synthetic pesticides which are harmful to human health and environment. This study investigated farmers’ preferences and willingness to pay (WTP) for attributes of integrated pest management (IPM) methods against S. frugiperda. A survey was conducted among 400 randomly selected maize farmers in eight districts of Benin using a questionnaire. Results showed that the majority of farmers (66.5%) who were interested in the IPM approach preferred a combined use of intercropping and ecological control products in managing S. frugiperda. Farmers who were more likely to pay for IPM strategies against S. frugiperda had less access to extension services, very small farms, and relatively low income. They represented 38.82% of the sample and were willing to pay additional protection costs of 4.53 US$/ha for the combination of several management methods, 86.09 US$/ha for the reduction of human health risks, 22.20 US$/ha for the preservation of environment, and 4.90 US$/ha for a reduction in yield losses. The policy implications of these findings for the extension of IPM technologies were discussed.
Keywords: fall armyworm; willingness to pay; integrated pest management; welfare; Benin